ASPEK BISNIS USAHA LAUNDRY SEPATU DI JAKARTA - Brastoro (Jurnal Manajemen, 2020)
Footish is a business engaged in laundry shoes by offering shoe washing services using Dry Cleaning methods. This business markets its business by disseminating information through social media in the form of Instagram and Facebook and the sneakers community in Jakarta. The initial investment requirement for Footish is Rp. 286,873,000 which is used to rent buildings for 1 year, equipment costs and equipment costs, as well as initial cash reserves. Proforma calculation of profit and loss for 5 years, namely from 2019 to 2023 shows a positive and visible number will always increase every year, as well as for the pro forma cash flow and pro forma balance sheet. The results of the analysis of the feasibility of Footish business prove that this business is quite feasible to run because judging from the break-even point analysis shows that the sales generated by Footish are greater than the value of BEP. Then the value of NPV is greater than zero, which is Rp. 495,893,250 using the credit interest rate of 11.83%. The IRR value obtained is 63.17% greater than the Expected Rate of Return of 11.83%. Payback Period analysis that shows the return on investment from this business is for 1 year 7 months 3 days. Keywords: Business Feasibility, BEP, Investment Feasibility, NPV, PI, PP, IRR